Quantitative investigation of vascular response to mesenteric venous thrombosis using large‐field‐of‐view photoacoustic microscopy. Issue 12 (21st August 2019) - Qin, Wei; Qi, Weizhi; Xi, Lei
Abstract: Mesenteric venous thrombosis (MVT) is one of major causes leading to severe mesenteric ischemia. Vascular network plays an important role during the occurrence and development of MVT. However, there lacks an appropriate imaging method, which features advanced volumetric resolving capability, superior sensitivity to hemoglobin, and ultra‐large field‐of‐view (FOV), to investigate vascular response of MVT. In this study, we developed and applied a large‐FOV optical resolution photoacoustic microscopy to quantify the vascular response during the entire course of two different MVT models in which we ligated the superior mesenteric vein and inferior mesenteric vein, respectively. Furthermore, we developed a quantitative algorithm to derive total vascular length, relative concentration of total hemoglobin and vascular density over the FOV to reveal different vascular responses in different MVT models. Abstract : We developed and applied a large‐field‐of‐view (FOV) optical resolution photoacoustic microscopy to quantify the vascular response during the entire course of two different mesenteric venous thrombosis (MVT) models. Furthermore, we developed a quantitative algorithm to derive total vascular length, relative concentration of total hemoglobin and vascular density over the FOV to reveal different vascular responses in different MVT models.